Stereotypes about the deaf and sign language in the thinking of special needs education students - KOCOŃ, MALWINA; SKALNY, MAGDALENA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Malwina Kocoń, Magdalena Skalny, Stereotypes about the deaf and sign language in the thinking of special needs education students. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 109-126. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.06 The article discusses the problems of deaf people, Polish sign language as well as Signed Polish (Manually-Coded Polish) in the context of stereotypes held by first year students of special needs education. The analysis of the results of empirical research indicates which of the stereotypes concerning deaf and sign language mentioned in the study are present in the thinking of the social group covered by the research and the frequency of their occurrence. It presents and explains terminological aspects regarding stereotypes and proposes postulates to eliminate negative stereotyping.